Efecto del medio de cultivo en la virulencia de Nomuraea rileyi sobre Spodoptera frugiperda (Lepidoptera: Noctuidae) - Caro C, L.F.=700 1 Villamizar R, L.F.; Espinel C, C.; Cotes, A.M.
(Es, En)
Ilus., 31 ref.
Keywords: NOMURAEA; HONGOS ENTOMOPATOGENOS; ENSAYO BIOLOGICO; VIRULENCIA; PATOGENICIDAD; SPODOPTERA FRUGIPERDA; LEPIDOPTERA; NOCTUIDAE; COLOMBIA